Facilitators and barriers to integrating physical health care during treatment for substance use: A socio‐ecological analysis. (23rd October 2020) - Osborne, Briony; Kelly, Peter J.; Robinson, Laura D.; Ivers, Rowena; Deane, Frank P.; Larance, Briony
Abstract: Introduction and Aims: Clinical practice guidelines recommend physical health be addressed when treating substance use disorders. Yet, the integration of alcohol and other drug (AOD) treatment and physical health care is seldom actualised. This is particularly the case in the non‐government sector. Using the socio‐ecological model as a framework, this study aimed to examine the facilitators and barriers to integrating physical health in non‐government AOD services. Design and Methods: Interviews were conducted with residential and outpatient AOD services across New South Wales, Australia. Qualitative data were collected from service users ( n = 20) and clinicians ( n = 13). Interview data were transcribed then systematically coded and analysed using iterative categorisation. Results: Most staff recognised physical health care as a fundamental component of treatment for substance use even when there were personal, professional and structural barriers for doing so. Service users reported a diverse range of health and social benefits when physical health care was incorporated in to AOD treatment. An exception to this was some negative experiences with health‐care providers that were not identified by staff. Discussion and Conclusions: Findings highlight the importance of developing resources to enhance the health literacy and capacity of non‐government AOD services to address the physical health of clients. Given some clients reported negative experiences with health‐care providers that were not identified by staff, services should seek regular feedback from clients regarding their experiences with external providers. The effectiveness of existing and new physical health initiatives within non‐government organisation AOD services needs more formal evaluation.